The Implementation of Islamic Character Education in Overcoming Bullying Behavior in Islamic Primary Schools - Ahmadi, Ahmadi (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2025)
The phenomenon of bullying in schools destroys the learning atmosphere and harms students' mental and emotional development. Even though Islamic character education has been implemented as part of the curriculum, cases of bullying still arise. This research aims to explore the implementation of Islamic character education in overcoming bullying behavior at SDIT Lampu Iman. Using qualitative methods and a case study approach, this research reveals that Islamic character education integrated into the curriculum and daily activities effectively reduces bullying incidents. This program involves important elements such as special training for teachers to recognize and handle bullying behavior and parental involvement in supporting Islamic character values at home. In addition, the school implements a safe and confidential reporting system for students who are victims or witnesses of bullying, so that they feel comfortable reporting incidents that occur. The research results showed a significant reduction in bullying incidents and positive changes in student behavior, such as increased empathy, solidarity, and cooperation. Hopefully, this research can significantly contribute to the development of Islamic character education programs in Integrated Islamic schools, creating a safe, supportive, and conducive learning environment for students' optimal development.